Wpływ wad zgryzu na zaburzenia artykulacji - Lisiecka, Patrycja; Piątkowska, Dagmara (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2015)
This article presents a review of the research conducted to date into the coexistence of malocclusions and phonation disorders, as well as the results of research conducted by the authors of the article. It is an attempt at providing answers to the following questions: are phonation disorders related to specific malocclusions, what specific phonation disorders accompany specific occlusal problems, does a single problem condition another occlusal problem? Detailed study of this subject will provide a concise compilation of knowledge for experts in many areas, including speech-language pathology, orthodontics, paediatrics, otolaryngology and phoniatrics. The article presents a specific approach to occlusion, namely from the speech-language pathology point of view. The authors have associated phonation disorders with specific malocclusions. Numerous clinical trials are necessary to investigate this phenomenon, to research the above mentioned dependence and identifying the relations between malocclusions and phonation disorders. The article presents the results of the research carried out by the authors together with results of surveys undertaken by professionals dealing with the impact of malocclusions on phonation disorders over the years.